Numerical study of vegetable oil as dielectric in the generation of surface plasmon polaritons in metal: The case of double interfaces (International Journal of Scientific Research and Management (IJSRM), 2022)
Modified electromagnetic waves which is resulted from coupling of surface plasmon and initial electromagnetic waves are called surface plasmon polaritons (SPP). These type of polaritons are generated at the interface between metal and dielectric. Many studies are performed since SPP have potential application in many fields. The process of generating SPP was usually using dielectrics in the form of solid. However, the usage of liquid dielectric in generating SPP is very rare. In this study, we predict numerically the usage of liquid dielectrics by solving the dispersion relation of the SPP. The dispersion relation was derived using Maxwell equations and the continuity of the fields at the interfaces. The metal was immersed in the liquid dielectrics. We used parameters of castor oil as liquid dielectric in the numerical calculation. We found that the dispersion relation had two branches. One branch represented in phase condition while the other branch illustrated out of phase condition. This result agree with the previous research using solid dielectric.